Metacognitive States in Language, Communication and Cognition - N. K. Ryabtseva (Научный диалог)
The article is devoted to the identification and description of meta-cognitive states, processes and operations and their role in language, communication, and cognition. It is shown that metacognitive states, and processes differ from strictly cognitive in three significant respects. First, they are reflexive in nature; second, they are divided into prototypical and derivative; third, they play a special role in language, communication and cognition. The main problem with this is the fact that metacognitive states can be expressed in language not only directly and explicitly, but they can be hidden, implicit, as well as syncretic with other important communicative meanings. Linguistic means of representing metacognitive phenomena highlighting their role in communication are systemized and characterized. It is indicated that language means, reflecting metacognitive states, are of various nature and show in particular how metacognitive states manifest themselves in behaviour and speech: the dreamy look , to watch closely , to refuse to recognize . The role of metacognitive states in learning and scientific knowledge is described. It is noted that verbalization of metacognitive processes in academic discourse is performed by means of expressions, showing the reflection of the knowing subject over produced mental operations: to define a problem , to suggest a hypothesis , to justify the relevance of a study , to sum up . In conclusion, it is emphasized that one of the most promising directions for future research of metacognitive problems is to compare and contrast knowledge and thinking, metacognition and “meta-thinking,” as well as the linguistic means of their verbalization.